ANALYSIS OF WOMEN'S GENDER EQUALITY IN HOUSEHOLD LIVELIHOODS OF DAIRY FARMERS POST-FOOT AND MOUTH DISEASE (FMD) - Fauzi, Muhammad; Sulistyati, Marina; Daud, Andre Rivianda (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Gender equality is an increasingly relevant issue for developing countries, including Indonesia. However, recognition of women's contribution to the livestock sector still needs to improve, which can affect their motivation to be more actively involved in the livestock business. The Foot and Mouth Disease (FMD) pandemic has become an additional challenge by causing a decrease in income from livestock activities. This research aims to examine the division of women's roles, analyze the impact of household characteristics on gender equality, and evaluate the level of gender integration among post-FMD livestock farmers. The research method used was simple random sampling and multinomial logit regression analysis. The research results show a change in the role of women who are more active in diversifying sources of income, as well as the influence of household characteristics on gender equality in access to economic opportunities. In addition, the level of gender integration among farmers after the FMD has shown a responsive level of 56% and a transformative level of 44%, reflecting positive developments in gender practices and awareness in the livestock sector.